2019
DOI: 10.1371/journal.ppat.1007583
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 signaling improves PD-1 blockade therapy during chronic viral infection

Abstract: CD8 T cells are necessary for the elimination of intracellular pathogens, but during chronic viral infections, CD8 T cells become exhausted and unable to control the persistent infection. Programmed cell death-1 (PD-1) blockade therapies have been shown to improve CD8 T cell responses during chronic viral infections. These therapies have been licensed to treat cancers in humans, but they have not yet been licensed to treat chronic viral infections because limited benefit is seen in pre-clinical animal models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…Interestingly, expression of TICAM2 (a TLR4 pathway adaptor protein, reviewed in ref. 45) was increased after pembrolizumab administration in patients who derived benefit on-study, which provides new insights into the potential cross-talk between the TLR4 and PD-1/PD-L1 pathways in viral infections (46).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, expression of TICAM2 (a TLR4 pathway adaptor protein, reviewed in ref. 45) was increased after pembrolizumab administration in patients who derived benefit on-study, which provides new insights into the potential cross-talk between the TLR4 and PD-1/PD-L1 pathways in viral infections (46).…”
Section: Discussionmentioning
confidence: 92%
“…Fourth, protein kinase C epsilon (PRKCE) is overexpressed in most solid tumors and plays critical roles in different cancer-associated pathways, including toll-like receptor 4 (TLR-4) signaling that plays a role in the induction of both innate and adaptive immunity [78]. TLR-4 signaling was recently shown to improve anti-PD-1 therapy during chronic viral infection [79]. Enzastaurin, a protein kinase C inhibitor, thus could be used to enhance anti-PD-1 therapy in melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…PD-1-based immunotherapy for the treatment of chronic infection was first shown in the chronic LCMV Cl-13 model (Barber et al, 2006), and was then shown to also be effective in the SIV model in macaques (Velu et al, 2009). Many studies on immune regulation have utilized the LCMV system (Bhattacharyya et al, 2017b;Bhattacharyya & Penaloza-MacMaster, 2017, 2018Im et al, 2016;Kamphorst et al, 2017;Penaloza-MacMaster et al, 2011;Penaloza-MacMaster, Kamphorst et al, 2014;Penaloza-MacMaster, Masopust, & Ahmed, 2009;Penaloza-MacMaster, Provine, Blass, & Barouch, 2015;Penaloza-MacMaster, Teigler et al, 2014;Vezys et al, 2011;Wang et al, 2019;West et al, 2013;West et al, 2011).…”
Section: Intravenous Infectionmentioning
confidence: 99%
“…Immunotherapies, such as PD-1/PD-L1/LAG-3 blocking antibodies, can be administered intraperitoneally, every 3 days (200 μg in 500 μl), five times. This dose is typically used in many experiments because it blocks all receptors for many inhibitory pathways (Blackburn et al, 2009;Penaloza-MacMaster, Kamphorst et al, 2014;Vezys et al, 2011;Wang et al, 2019;West et al, 2013). However, if testing a novel monoclonal antibody in vivo, titration may be needed to determine the saturating dose.…”
Section: The Conventional Cl-13 Modelmentioning
confidence: 99%